2020
DOI: 10.1002/admi.202000999
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Trends in Chemically Doped Graphene

Abstract: Chemically doped graphene materials are fascinating because these have different desirable attributes with possible synergy. The inert and gapless nature of graphene can be changed by adding a small number of heteroatoms to substitute carbon in the lattice. The doped material may display superior catalytic activities; durable, fast, and selective sensing; improved magnetic moments; photoresponses; and activity in chemical reactions. In the current review, recent advances are covered in chemically doped graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 197 publications
(402 reference statements)
4
57
0
Order By: Relevance
“…On the one hand, the feasibility of chemical synthesis methods is limited since structural doping and modification are usually required to be performed in the process of devices fabrication. Presently, only the Ge nanoparticles/graphene nanocomposites are obtained by the chemical synthesized method [ 49 , 50 ] since the heavy elements are very difficult to be introduced into graphene lattice by the chemical synthesis method [ 51 ]. The implantation of Ga/Ge/As can demonstrate the possibility to tune the structural, electrical, optical and magnetic properties of graphene for applications in electronic, optoelectronic and sensing devices [ 31 , 52 , 53 , 54 , 55 ], which would be proved to be a more effective way than other synthesis techniques.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the feasibility of chemical synthesis methods is limited since structural doping and modification are usually required to be performed in the process of devices fabrication. Presently, only the Ge nanoparticles/graphene nanocomposites are obtained by the chemical synthesized method [ 49 , 50 ] since the heavy elements are very difficult to be introduced into graphene lattice by the chemical synthesis method [ 51 ]. The implantation of Ga/Ge/As can demonstrate the possibility to tune the structural, electrical, optical and magnetic properties of graphene for applications in electronic, optoelectronic and sensing devices [ 31 , 52 , 53 , 54 , 55 ], which would be proved to be a more effective way than other synthesis techniques.…”
Section: Resultsmentioning
confidence: 99%
“…This type of modification is applicable when total preservation of graphene's natural conductivity is not necessary, such as in tuning of graphene's solubility, anti-bacterial activity, or surface chemical reactivity. Covalent modifications can also be obtained via doping heteroatoms onto the graphene lattice [101][102][103]. Furthermore, for graphene produced via the oxidation-reduction method, the partial reduction results in oxygen-containing functionalities grafted at the graphene surface, also permitting covalent modifications [104].…”
Section: Graphene Functionalizationmentioning
confidence: 99%
“…The Dirac equation describes the electron transport in graphene to explain the mobility of charge carriers [13,14]. Several graphene doping methods have been investigated in recent studies that include chemical doping, electrochemical doping, ion or electron beam irradiation, metal decoration or deposition, electrostatic doping, electrical stress-induced doping, absorption and desorption of gas molecules, and ultra-violet (UV) light illumination [14][15][16][17][18][19][20][21][22][23][24][25]. Graphene surface doping, without effect on the honeycomb structure which can be caused by other methods including chemical doping or the absorption and desorption of gas molecules, is usually unstable under experimental conditions and in a laboratory atmosphere [18,19,26].…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods, including e-beam irradiation or plasma treatment of graphene, that can be applied to tune its electrical properties but these result in local defect formations in the graphene and affect its chemical properties [17,20,26]. Although there are some studies that have been reported on the carrier doping of the graphene by deep ultra-violet (DUV) irradiation, the effect of DUV on graphene is yet to be thoroughly explored [20,[22][23][24][25]27]. The experimental conditions under which DUV irradiation is carried out can introduce either p or n-type stable or reversible doping to the graphene [20,[22][23][24][25]27].…”
Section: Introductionmentioning
confidence: 99%